Design and Building of Gas Analyzer - Turman, Ibrahim; Hroush, Riyad (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2013)
Gas concentration measurements have gained more and more attention in the old of industrial process control and environmental pollution monitoring. Industrial process produce many gases; some of these gases are toxic and harmful for human and environment. So the need for a device to measure the percentage of more than one gas in many fields and application with low cost is a challenge. In this project a gas analyzer device for nine different gasses (CO , Alcohol , CO2 , O3, NH3 , LPG , H2 , CH4 ) will be built using sensors connected with computer to analyze and display the results. The MATLAB software was used to process the data from the sensors and then display the results on computer screen.
CD , no of pages 84, 26820, ميكانيك 4/2013, IN THE STORE
Keywords: Gas Analyzer - Design and Building